Fate of laparoscopic morcellation post-FDA warning: a literature review - Deepak Bose (International Journal of Medical Research and Review, 2016)
In laparoscopy, tissue extraction might require morcellation for larger intra-abdominal specimens, especially in gynecological patients. specimen, the specimen needs to be reduced. The Food and Drug Administration (FDA) issued a press release in April 2014 that discouraged the use of devices used for morcellation - power morcellators. This article has the objective to review the literature related to complications by power morcellation of uterine fibroids in laparoscopy and offer recommendations to laparoscopic surgeons in gynaecology. Respecting women who have leiomyosarcoma, it can be concluded that the FDA directive was based on a misleading analysis due to inherent flaws in the trials analysed by it. Hence, the need of the hour are more accurate estimates regarding the prevalence of leiomyosarcoma among women having surgery for presumed leiomyomas. Modification of the FDA’s current restriction regarding power morcellation would empower each woman to allow surgeons and hospitals to make the most appropriate, informed choices regarding utilization of tissue extraction in individual patients undergoing uterine surgery without undermining the freedom of the woman to choose the best-suited procedure.